The wrecker - Cussler, Clive; Scott, Justin (New York : G.P. Putnam's Sons, 2009)
Investigating a series of attacks on the Southern Pacific Railroad's Cascades express lines, Detective Bell learns of the existence of an elusive saboteur who recruits and murders his own accomplices while engineering schemes of maximum havoc.
Map on lining papers
Keywords: Bell, Isaac -- (Fictitious character) -- Fiction; Private investigators -- Fiction; Sabotage -- Fiction; Railroad trains -- Fiction; West (U.S.) -- History -- 20th century -- Fiction; Adventure fiction; Suspense fiction